Kurt Eisner : a modern life - Gurganus, Albert E. (German history in context., 2018)
The first comprehensive biography in English of the leader of the Bavarian Revolution and Republic of 1918/19, the first Jewish head of a European state and a man who embraced and embodied modernity.